Peran Organizational Citizenship Behavior (OCB) dalam Peningkatan Kinerja Karyawan : Sebuah Kajian Literatur - Kiki Nur Azizah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to conduct a literature review examining the influence of Organizational Citizenship Behavior (OCB) on job satisfaction and employee performance. Through a thorough analysis of relevant literature, this article presents significant findings from previous research. The analysis of three relevant journals reveals that OCB has a significant positive influence on job satisfaction. When employees voluntarily engage in OCB behaviors that go beyond their formal job responsibilities, it tends to enhance their job satisfaction. Additionally, OCB is positively related to employee performance. Employees who engage in OCB behaviors tend to achieve better performance in various aspects of their work. In the context of education, OCB also plays a crucial role in improving teacher performance and creating a productive learning environment. Previous studies have shown that teacher OCB behaviors, such as assisting fellow teachers, providing emotional support to students, and actively participating in extracurricular activities, contribute to enhanced teacher performance and student academic achievement. This article provides an in-depth understanding of the importance of OCB in enhancing job satisfaction and employee performance. To create a positive and productive work environment, organizations need to encourage and appreciate OCB behaviors through recognition, appreciation, and increased participation opportunities. Although previous research findings demonstrate a positive relationship between OCB, job satisfaction, and employee performance, it is important to note that further research is needed to gain a deeper understanding of the factors influencing OCB and the best strategies for fostering OCB behaviors in the workplace. Through a greater understanding of OCB, organizations can create a positive and empowering work environment where employees feel satisfied with their jobs and achieve optimal performance.